1989
DOI: 10.1152/jappl.1989.67.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Use of doubly labeled water technique in soldiers training for jungle warfare

Abstract: The doubly labeled water method was used to estimate the energy expended by four members of an Australian Army platoon (34 soldiers) engaged in training for jungle warfare. Each subject received an oral isotope dose sufficient to raise isotope levels by 200-250 (18O) and 100-120 ppm (2H). The experimental period was 7 days. Concurrently, a factorial estimate of the energy expenditure of the platoon was conducted. Also, a food intake-energy balance study was conducted for the platoon. Mean daily energy expendit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
2

Year Published

1991
1991
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 6 publications
5
17
2
Order By: Relevance
“…The mean TEE observed in our subjects in hot dry conditions, according to the DLW method (23 MJ), was slightly higher than that reported in other studies [e.g. the 20 MJ, observed in hot wet conditions in soldiers training for jungle warfare (Forbes-Ewan et al 1989), the 21 MJ reported during strenuous activity in a moderately cold environment (Hoyt et al 1991), and the 14 MJ observed in the temperature range A1.1 to 16°C during ®eld training of special operations soldiers (Delany et al 1989)]. Thus, the energy requirements of subjects doing exercise in hot dry environments may be greater than when exercising in temperate environments.…”
Section: Discussioncontrasting
confidence: 81%
“…The mean TEE observed in our subjects in hot dry conditions, according to the DLW method (23 MJ), was slightly higher than that reported in other studies [e.g. the 20 MJ, observed in hot wet conditions in soldiers training for jungle warfare (Forbes-Ewan et al 1989), the 21 MJ reported during strenuous activity in a moderately cold environment (Hoyt et al 1991), and the 14 MJ observed in the temperature range A1.1 to 16°C during ®eld training of special operations soldiers (Delany et al 1989)]. Thus, the energy requirements of subjects doing exercise in hot dry environments may be greater than when exercising in temperate environments.…”
Section: Discussioncontrasting
confidence: 81%
“…It seems that the more subject is more active, the greater difference was occurred (Table 3). This phenomenon is not surprising, as findings from previous research have demonstrated similar disparity of El in subjects monitored over field-like measurement periods [23,24]. This study provides information on the degree of discrepancy of El that occurs in healthy, non-obese individuals.…”
Section: Discussionsupporting
confidence: 82%
“…Both the men and the women were able to sustain physical activity level (PAL) values of 3.4-3.5, well above what is considered the upper limit of sustainable metabolic rate for the general (nonmilitary) population (26). The PAL during the Crucible was 42% higher than that observed (2.5-2.8) in other military field training exercises (2,5,7,11,12,14). Hoyt et al did find an average PAL of 4.0 during the initial 4 d of training in a cold, mountainous environment (11), but these values declined during subsequent days.…”
Section: Discussionmentioning
confidence: 79%